Sejarah Penulisan Al-Qur'an: Pembukuan Dan Pembakuannya - Ismail, Affan; Affan Ismail; Imam Walid Asrofuddin Ulil Huda; Muhamad Yusrul Hana (FIHROS: Jurnal Sejarah dan Budaya, 2025)
The Quran is God's holy book that was revealed to Muhammad as the last prophet and apostle. This paper with the title ‘History of the Writing of the Quran; Bookkeeping and Standardization’ seeks to present scientific work that contributes to the repertoire of Quran Science. This paper also aims to contribute to presenting the scientific truth of the authenticity of the Quran seen from a historical perspective. Academic work that produces this scientific work uses the Library Study method with a qualitative approach. The result of this paper is the history of the bookkeeping and standardization of the Qur'an has proven that the Qur'an is very well preserved from the time of its revelation to the time of its printing. Likewise, the content in the Quran itself can detail the story of the past which is very far from the time of the Prophet Muhammad, but the fact of the truth of the story is proven long after the time of the Prophet Muhammad. The continuity of historical events that have proven that Allah is the one who keeps the Qur'an.